1986
DOI: 10.1016/0092-8674(86)90805-6
|View full text |Cite
|
Sign up to set email alerts
|

A transcription terminator located upstream of the mouse rDNA initiation site affects rRNA synthesis

Abstract: Mouse ribosomal genes have a short sequence upstream of the transcription initiation site that is related in structure and function to the terminator boxes previously identified at the 3' end of the transcription unit. This upstream terminator recognizes the same protein factor as the 3'-terminal sites and is able to terminate RNA polymerase I transcription in vitro. S1 mapping and nucleolar run-on experiments reveal the presence of 5'-terminal spacer transcripts that are terminated at this site. These transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
114
1

Year Published

1987
1987
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(118 citation statements)
references
References 26 publications
3
114
1
Order By: Relevance
“…The mouse Sal box is an 18-bp element repeated 10 times in the IGS, while humans contain a shorter Sal box (11 bp) that is recognized by the human TTF-I (Bartsch et al 1987;Pfleiderer et al 1990;. Several mammalian rDNAs contain a Sal box (T0) upstream of the transcription start site (Grummt et al 1986;Labhart and Reeder 1986;Pfleiderer et al 1990). Such terminators seem to prevent transcriptional interference by terminating transcripts initiated in the IGS (Bateman and Paule 1988;Henderson et al 1989) and have been shown to stimulate transcription as well (Grummt et al 1986).…”
Section: Rnapi Terminationmentioning
confidence: 99%
See 1 more Smart Citation
“…The mouse Sal box is an 18-bp element repeated 10 times in the IGS, while humans contain a shorter Sal box (11 bp) that is recognized by the human TTF-I (Bartsch et al 1987;Pfleiderer et al 1990;. Several mammalian rDNAs contain a Sal box (T0) upstream of the transcription start site (Grummt et al 1986;Labhart and Reeder 1986;Pfleiderer et al 1990). Such terminators seem to prevent transcriptional interference by terminating transcripts initiated in the IGS (Bateman and Paule 1988;Henderson et al 1989) and have been shown to stimulate transcription as well (Grummt et al 1986).…”
Section: Rnapi Terminationmentioning
confidence: 99%
“…Several mammalian rDNAs contain a Sal box (T0) upstream of the transcription start site (Grummt et al 1986;Labhart and Reeder 1986;Pfleiderer et al 1990). Such terminators seem to prevent transcriptional interference by terminating transcripts initiated in the IGS (Bateman and Paule 1988;Henderson et al 1989) and have been shown to stimulate transcription as well (Grummt et al 1986). Yeast rDNA also contains a T0 terminator, which is, however, in the wrong orientation to mediate termination (Fig.…”
Section: Rnapi Terminationmentioning
confidence: 99%
“…They are transcribed by a specific enzyme, RNA polymerase I, and they are arranged in a tandem array. This unique genetic structure has led to speculation that transcription of an individual gene is not independent of transcription of the neighboring genes; e.g., termination at one transcription unit may lead directly to initiation at the neighboring downstream promoter (7,12,15, 26).We have identified a sequence element, specific for RNA polymerase I, that has many of the characteristics of an RNA polymerase II enhancer (9, 10). In this paper, we explore aspects of the function of RNA polymerase I and its enhancer to ask about the parallels between polymerase I and polymerase II enhancers and about the importance of the tandemness of rRNA genes to polymerase I activity.…”
mentioning
confidence: 99%
“…In the mouse, a repetitive set of termination sequences (Sall boxes) have been identified about 600 bp downstream of the 3' end of the 28S rRNA-coding region (13). Yet another Sail box is found just upstream of the initiation site; its presence stimulates transcription substantially (12,15). A termination sequence upstream of the promoter stimulates transcription of a Xenopus rRNA gene even when no upstream transcription unit is present (24).…”
mentioning
confidence: 99%
See 1 more Smart Citation